2019
DOI: 10.1021/acs.est.9b00245
|View full text |Cite
|
Sign up to set email alerts
|

Size Distribution and Depolarization Properties of Aerosol Particles over the Northwest Pacific and Arctic Ocean from Shipborne Measurements during an R/V Xuelong Cruise

Abstract: Atmospheric aerosols over polar regions have attracted considerable attention for their pivotal effects on climate change. In this study, temporospatial variations in single-particle-based depolarization ratios (δ: s-polarized component divided by the total backward scattering intensity) were studied over the Northwest Pacific and the Arctic Ocean using an optical particle counter with a depolarization module. The δ value of aerosols was 0.06 ± 0.01 for the entire observation period, 61 ± 10% lower than the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The individual aerosol particle type was identified according to both the particle size and the depolarization property. The POPC is capable of distinguishing four types of aerosols, as shown in Figure 1: (1) anthropogenic pollution particles with Dp < 1 μm and δ < 0.2 or 1 μm < Dp < 2.5 μm and δ < 0.1; (2) coarse-mode mineral dust with Dp > 2.5 μm and δ ¼ 0.3 ± 0.1 and fine-mode dust with Dp < 1 μm and δ > 0.2 or 1 μm < Dp < 2.5 μm and δ > 0.1; (3) polluted dust with Dp > 2.5 μm and δ < 0.2; and (4) sea salt particles with 1 μm < Dp < 2.5 μm and δ < 0.1 (Kobayashi et al, 2014;Pan et al, 2015Pan et al, , 2016Tian et al, 2018Tian et al, , 2019. All external and internal mixing processes of dust events can be captured by the POPC.…”
Section: Introductionmentioning
confidence: 99%
“…The individual aerosol particle type was identified according to both the particle size and the depolarization property. The POPC is capable of distinguishing four types of aerosols, as shown in Figure 1: (1) anthropogenic pollution particles with Dp < 1 μm and δ < 0.2 or 1 μm < Dp < 2.5 μm and δ < 0.1; (2) coarse-mode mineral dust with Dp > 2.5 μm and δ ¼ 0.3 ± 0.1 and fine-mode dust with Dp < 1 μm and δ > 0.2 or 1 μm < Dp < 2.5 μm and δ > 0.1; (3) polluted dust with Dp > 2.5 μm and δ < 0.2; and (4) sea salt particles with 1 μm < Dp < 2.5 μm and δ < 0.1 (Kobayashi et al, 2014;Pan et al, 2015Pan et al, , 2016Tian et al, 2018Tian et al, , 2019. All external and internal mixing processes of dust events can be captured by the POPC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have demonstrated that aerosols transported to the Arctic Ocean originated from multiple sources (Toledano et al, 2012), such as biomass burning in the northern region (Stohl & Sodemann, 2010), agricultural fires in Eastern Europe (Myhre et al, 2007; Treffeisen et al, 2007), and pollution and dust from Asia (Di Pierro et al, 2011). The depolarization properties and mixing state of atmospheric aerosols at the sea level over the Arctic Ocean were investigated by Tian et al (2019). Furthermore, Zhan et al (2010) evaluated the spatiotemporal characteristics of aerosols and the sources and climatic effects of black carbon in the Arctic region, suggesting that Arctic black carbon aerosols can affect the geothermal radiation balance as well as snow and in particular, snow albedo.…”
Section: Introductionmentioning
confidence: 99%